2007
DOI: 10.1038/sj.bjc.6603623
|View full text |Cite
|
Sign up to set email alerts
|

Cigarettes and alcohol in relation to colorectal cancer: the Singapore Chinese Health Study

Abstract: The relations were examined between colorectal cancer and cigarette smoking and alcohol consumption within the Singapore Chinese Health Study, a population-based, prospective cohort of 63 257 middle-aged and older Chinese men and women enrolled between 1993 and 1998, from whom baseline data on cigarette smoking and alcohol consumption were collected through in-person interviews. By 31 December 2004, 845 cohort participants had developed colorectal cancer (516 colon cancer, 329 rectal cancer). Compared with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 25 publications
10
97
1
2
Order By: Relevance
“…Recent analyses within the Singapore Chinese Health Study have shown that smoking is only a risk factor for rectal cancer (2). We now report that among carriers of the XRCC1 Trp 194 -Arg 399 haplotype, smoking is also a risk factor for colon cancer, in addition to rectal cancer.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Recent analyses within the Singapore Chinese Health Study have shown that smoking is only a risk factor for rectal cancer (2). We now report that among carriers of the XRCC1 Trp 194 -Arg 399 haplotype, smoking is also a risk factor for colon cancer, in addition to rectal cancer.…”
Section: Discussionmentioning
confidence: 74%
“…Previously, using the entire cohort database, we reported on the associations between tobacco/alcohol use and colorectal cancer risk (2). Table 1 shows the frequencies of cases and controls by levels of smoking and alcohol consumption within the present nested case-control study set.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations